Functional characterization and physiological significance of SETD3 - Chia, Shyh Jenn (2017)
Lysine methyltransferase family plays important roles in various cellular processes, for instance transcriptional regulation, embryonic development, cell proliferation, migration and more. My project aims to characterize a novel SET-domain containing lysine methyltransferase SETD3 and understand the physiological significance of this protein. SET-domain containing protein SETD3 methylates Lys-4 and Lys-36 of histone 3, which is linked to the transcriptional activation. In addition, SETD3 also comprises of Rubisco LSMT C-terminal substrate binding domain that could potentially facilitate binding to non-histone substrate. In our preliminary studies, we identified that SETD3 was able to methylate a 42kDa protein in the cytosolic fraction. According to the size estimation, we conducted SETD3 methylation assays with monomeric and polymeric form of actin. The result showed that monomeric and polymeric actin were the potent substrates of SETD3. From other studies, actin is shown to be methylated at Lys-84 and Lys-326 but the methyltransferases responsible for these methylations remain unknown. In the assays using actin mutants with Lys-84, Lys-326 or Lys-328 to alanine substitutions as substrate, SETD3 methylation activity was not reduced, suggesting that these lysines are unlikely to be the SETD3 target sites. In addition, SETD3 expression in B cells increased after the stimulation with anti-IgM antibodies, thymus-dependent signal CD40 and lipopolysaccharides (LPS). The preliminary flow cytometry immunophenotyping also revealed perturbed development of T cells, B cells, and neutrophils in the conditional SETD3-deficient mice (Mx-cre). These results suggest that SETD3 may play physiological roles in the development, activation, and effector functions of various immune cells. In future, the physiological function of SETD3 in the development of immune cells and immune responses will be further examined using our conditional knockout mouse model.